2020
DOI: 10.3390/polym12061347
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Supercritical CO2 Extraction as a Method for Plastic Waste Decontamination

Abstract: Due to the lack of advanced methods to clean plastic waste from organic contaminants, this study aimed at evaluating supercritical extraction as a decontamination method. Oil-adhesive high-density polyethylene (HD-PE) oil containers were subjected to supercritical extraction using supercritical carbon dioxide. The extraction was conducted at 300 bar, applying various temperatures (i.e., 70, 80 and 90 °C). The study assessed the impact of temperature on the decontamination efficiency. The variation in the sampl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Operational parameters of pressure, temperature, and time were selected according to previous studies reported in the literature. 12,21,22 The following experimental design was considered: (i) effect of matrix and effect of time -PET, PLA, and PP were processed at 80 °C and with varying times of 10, 30, and 60 min; (ii) effect of temperature -PP was processed for 30 min at 60, 70, and 80 °C; (iii) assessment of the reproducibility of the scCO 2 extraction -PP matrix at 80 °C for 30 min was processed in triplicate.…”
Section: Decontamination By Sccomentioning
confidence: 99%
See 1 more Smart Citation
“…Operational parameters of pressure, temperature, and time were selected according to previous studies reported in the literature. 12,21,22 The following experimental design was considered: (i) effect of matrix and effect of time -PET, PLA, and PP were processed at 80 °C and with varying times of 10, 30, and 60 min; (ii) effect of temperature -PP was processed for 30 min at 60, 70, and 80 °C; (iii) assessment of the reproducibility of the scCO 2 extraction -PP matrix at 80 °C for 30 min was processed in triplicate.…”
Section: Decontamination By Sccomentioning
confidence: 99%
“…Supercritical fluids, particularly supercritical CO 2 (scCO 2 ), have been studied for the extraction of plastics with analytical purposes; that is, targeting the analysis of the plastic composition, namely additives and oligomers. [17][18][19][20] As a technology to decontaminate POs for recycling, scCO 2 was applied for PP, 12,21 highdensity polyethylene, 22 linear low-density polyethylene (LLDPE), 12,23 and low-density polyethylene. 24 A theoretical model to analyse extraction yields considering the mechanisms of diffusion through the polymer matrix and the solubility in scCO 2 was developed.…”
Section: Introductionmentioning
confidence: 99%
“…To prevent cross-contamination, only glassware was used to conduct the extraction, treatment and analysis of samples. In order to analyse the PAH content in the plastic matrix, samples underwent extraction following the method reported by Alassali et al 26 Randall hot extraction was used as suggested by Geiss et al 20 The PAH content analysis was conducted on the extract aer applying a clean-up and drying steps (as explained below).…”
Section: Analysis Of the Pah Content In The Plastic Samplesmentioning
confidence: 99%
“…Finally, a solvent recovery step (evaporation step) was applied at 170 C, until the target volume of #20 mL was reached. 26,28 Aer the evaporation step, the reaction vessels were cooled down to room temperature. An internal standard solution was added to the solution to calculate the recovery.…”
Section: Analysis Of the Pah Content In The Plastic Samplesmentioning
confidence: 99%
See 1 more Smart Citation